Obtenção e caracterização de bioadsorventes a partir de algas marinhas para remoção de cromo hexavalente em solução aquosa - Gomes, Luana Mirtes de Freitas (2019)
The environment, over the last decades, has been affected by the population increase and the intense industrialization of the global economy. As a consequence, there is a significant increase in pollution of the various planetary ecosystems. Among the pollutants generated by industries, toxic metals can be highlighted for their deleterious effects on living organisms. When toxic metal ions are released as industrial waste, in water, soil or air, they can be absorbed by plants and animals, causing poisoning along the food chain, which can reach man. Hexavalent chromium is one of the most studied among the toxic metals due to its serious effects on human health. Several processes of pollutant removal in aqueous environments have been proposed and adsorption is one of the most attractive due to its versatility and wide ability to remove metals and other pollutants. In this context, algae biomass has been one of the most studied alternative materials for this process. This is due to the composition of its cell wall, which is rich in functional groups, which may be interesting for the adsorption process, such as: carboxylic (-COOH), sulfonic (-SO3H) and hydroxyl (-OH). This paper aims to test and compare three different types of seaweed - brown algae, Dictyota Mertensii (DM); red algae, Gracilaria Cervicornis (GC); and green algae, Ulva Fasciata (UV) - for hexavalent chromium adsorption in aqueous solution. The materials were characterized by granulometry, scanning electron microscopy (MEV), Fourier transform infrared spectroscopy (FTIR); Afterwards, kinetic and equilibrium studies were performed, fitting kinetic and adsorption isotherm models. Adsorption tests showed that the maximum adsorption capacity of hexavalent chromium at equilibrium and temperature of 58°C and initial concentrations ranging from 25 to 1000 mg/L was: 332 mg/g for DM; 296 mg/g for GC and 193.5 mg/g for UF. As for the description of the kinetics, the model that best fit the DM data was the pseudo-first order; for GC and UF was Elovich's model. Regarding the equilibrium data, the models that best described the experimental results were Langmuir (28 and 48 °C) and Freundlich (38 and 58 °C) for DM algae; while for GC algae the Toth (28°C), Langmuir (38°C), Sips (48°C) and Temkin (58°C) models were the best fit; For UF algae, the models that best fit were those of the Langmuir (28 and 38 °C) and Freundlich (48 and 58 °C) isotherms. The results showed that bioadsorbents obtained from seaweed have potential for hexavalent chromium removal under the investigated conditions. Being the most efficient material obtained from brown algae, DM.